5′-Noraristeromycin C-Nucleosides Based on Imidazo[1,2-a]pyrazine - Ye, Wei; Schneller, Stewart W. (Synthesis, 2015)
The preparation of two C-5′-nor-3-deazaaristeromycin diastereomeric analogues possessing a bridgehead nitrogen is described from (3aR,4R,6S,6aS)-2,2-dimethyl-6-vinyltetrahydro-3aH-cyclopenta[d][1,3]dioxol-4-ol that served as the cyclopentyl unit of the target carbocyclic nucleosides and as the scaffold upon which the compounds were built. The process evolved via a de novo approach for constructing the requisite fused imidazo unit between the aforementioned cyclopentyl ring and a readily available 2,3-dichloropyrazine. The syntheses were accomplished in 11 and 8 steps depending on the diastereomer sought.
Keywords: formycin; carbocyclic nucleosides; bridgehead nitrogen nucleoside base